Cooperation or conflict? problematizing organizational overlap in Europe - Galbreath, David J.; Gebhard, Carmen (Ashgate Pub., 2010)
This book examines the way NATO, OSCE, Council of Europe relate to and interact with each other, identifying the areas of positive convergence and divergence as well as areas of negative cooperation and conflict.